The Behavior of Terbuthylazine, Tebuconazole, and Alachlor during Denitrification Process - Kristína Pániková; Zuzana Bílková; Jitka Malá (MDPI AG, 2023)
Pesticide compounds can influence denitrification processes in groundwater in many ways. This study observed behavior of three selected pesticides under denitrifying conditions. Alachlor, terbuthylazine, and tebuconazole, in a concentration of 0.1 mL L−1, were examined using two laboratory denitrifications assays: a "short" 7-day and a "long" 28-day test. During these tests, removal of pesticides via adsorption and biotic decomposition, as well as the efficiency of nitrate removal in the presence of the pesticides, were measured. No considerable inhibition of the denitrification process was observed for any of the pesticides. On the contrary, significant stimulation was observed after 21 days for alachlor (49%) and after seven days for terbuthylazine (40%) and tebuconazole (36%). Adsorption was in progress only during the first seven days in the case of all tested pesticides and increased only negligibly afterwards. Immediate adsorption of terbuthylazine was probably influenced by the mercuric chloride inhibitor. A biotic loss of 4% was measured only in the case of alachlor.